Respuesta :

Step-by-step explanation:

hope it's helpful for you

pls mark me as brainliest

try the 2nd one by yourself

Ver imagen Аноним

Step-by-step explanation:

first of all we have to turn the "y" into a negative number so we multiply it by a negative number

11x+5y = 9..........................(1) × -3

11x+3y = 1.......................(2) × 5

and then we add the new equations

-33x - 15y = -27................(3)

55x+ 15y = 5........................(4)

eventually the y will be a "0" which has no value so it's pointless

22x = -22

x = -1

and then substitute y

11x +5y = 9

(11×-1) +5y =9

-11 +5y = 9

5y = 9 +11

5y = 20

y = 20÷5

y = 4

ACCESS MORE